Pembelajaran Seni Teater Tradisional Menggunakan Metode Role Playing di Kelas X SMA Negeri 1 Rambang Dangku - Astari, Maresta; NAD, Nugroho; Adoma, Auzy Madona (Indonesian Research Journal on Education, 2023)
Learning traditional theater arts in class X SMA Negeri 1 Rambang Dangku using the role-playingmethod is carried out with data validity techniques through observation, interviews, and documentation. Here the researcher gets class X to be studied, assisted by Mr. Ade Setiawan. S.Pd. as a cultural arts teacher to complete the research. The role-playing method is a role-playing method which means that the learning method is part of a simulation that is directed to express historical events, and create actual events or events that will appear in the future. In learning traditional theater arts in class X 1 the material learned is reading scripts that are more directed to realist scripts.